2020
DOI: 10.1177/1056789520904093
|View full text |Cite
|
Sign up to set email alerts
|

A coupled elastoplastic anisotropic damage model for rock materials

Abstract: In this study, a rigorous constitutive model within the framework of thermodynamics is formulated to describe the coupling process between irreversible deformation and anisotropic damage of rock materials. The coupling effect is reflected based on the “two-surface” formulation. The plastic response is described by a yield function while the anisotropic damage is defined by a novel exponential damage criterion. In the proposed model, another feature lies in introducing parameters β and k in the proposed model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Rocks may gradually accumulate damage deformation under external load, causing severe plastic deformation or even progressive failure (Krajcinovic et al, 1991;Liu et al, 2020;Su et al, 2019;Wang and Xu, 2020;Wu et al, 2019). The deformation and failure processes of rock, with many cracks and voids, are accompanied by energy release in the form of vast elastic waves (Ebrahimian et al, 2019;Feng et al, 2020;Hu et al, 2019;Wang et al, 2015;Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rocks may gradually accumulate damage deformation under external load, causing severe plastic deformation or even progressive failure (Krajcinovic et al, 1991;Liu et al, 2020;Su et al, 2019;Wang and Xu, 2020;Wu et al, 2019). The deformation and failure processes of rock, with many cracks and voids, are accompanied by energy release in the form of vast elastic waves (Ebrahimian et al, 2019;Feng et al, 2020;Hu et al, 2019;Wang et al, 2015;Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…7: where p is the plastic hardening variable and is the damage variable. Though a few studies proposed that the plastic and damage evolution are fully coupled (Salari et al 2004;Chen et al 2010;Wang and Xu 2020), based on the observation in Sect. 3.3, it is suggested that damage and plasticity are not so closely related.…”
Section: Constitutive Modellingmentioning
confidence: 99%
“…Several factors including F-T duration, F-T cycle and F-T temperature have also influence the mechanical behaviors of rock. For freeze-thawed rocks, several damage evolution models, using the uniaxial compressive strength (UCS) (Takarli et al, 2008), elastic modulus (Takarli et al, 2008;Wang and Xu, 2020), porosity (Zhang et al, 2018), P-or S-velocities (Hori and Morihiro, 1998), acoustic emission activities (Tian et al, 2021), rock strain (Li et al, 2020), and mass loss rate (Nicholson and Nicholson, 2000;Zhang et al, 2018), have been proposed to describe the F-T fatigue damage. However, almost all those studies are focused on intact rock subjected to freezethaw treatment, and the freeze-thaw responses of the naturally fractured rocks are not well understood.…”
Section: Introductionmentioning
confidence: 99%